The association between education and risk of major cardiovascular events among prostate cancer patients: a study from the Diet, Cancer and Health study. (4th May 2019) - Moustsen, Ida Rask; Friberg, Anne Sofie; Larsen, Signe Benzon; Duun-Henriksen, Anne Katrine; Tjønneland, Anne; Kjaer, Susanne K.; Brasso, Klaus; Johansen, Christoffer; Dalton, Susanne Oksbjerg
Abstract: Background: High socioeconomic position is associated with better prognosis in prostate cancer patients but it is unknown if part of this association may be explained by socioeconomic differences in severe late effects. We investigated the association between education as an indicator for socioeconomic position and cardiovascular events after prostate cancer and if such associations were mediated by differences in lifestyle, cardiovascular risk factors and prostate cancer treatment. Material and methods: We identified 1980 men diagnosed with prostate cancer from 1993 to 2014 among participants in the Danish Diet, Cancer and Health study. Individual level information on education, lifestyle, cardiovascular risk factors and prostate cancer clinical information were obtained from questionnaires, registries and medical records. The Cox proportional hazards models were used to evaluate the risk of incident acute myocardial infarction, ischemic stroke and heart failure during up to 18 years of follow-up for men with short (<9 years) or medium (9–12 years) compared with long education (>12 years). Results: Compared to men with long education, we found an increased risk of acute myocardial infarction in men with medium and short education (HR 3.14, 95% CI 1.53–6.47 and HR 2.14, 95% CI 0.82–5.58, respectively). Adjusting for stage, first-line treatment, lifestyle and cardiovascular risk factors did not change the HRs substantially (adjusted HRs 3.04, 95% CI 1.47–6.31 and 2.07, 95% CI 0.78–5.53, respectively). There were no educational differences in risk for ischemic stroke or heart failure. Conclusions: The risk of acute myocardial infarction was increased in prostate cancer patients with short or medium education compared with long education. Although the educational inequality did not seem to be explained by differences in treatment, lifestyle or cardiovascular risk factors, monitoring of cardiovascular health and health promotion should involve all prostate cancer patients regardless of social position to ensure best prognosis for all.